Family-based treatment of eating disorders in adolescents: current insights - Rienecke RD (Dove Medical Press, 2017)
Renee D Rienecke1–3 1Department of Pediatrics, 2Department of Psychiatry and Behavioral Sciences, College of Medicine, Medical University of South Carolina, Charleston, SC, 3Department of Psychiatry, University of Michigan Health System, Ann Arbor, MI, USA Abstract: Eating disorders are serious illnesses associated with significant morbidity and mortality. Family-based treatment (FBT) has emerged as an effective intervention for adolescents with anorexia nervosa, and preliminary evidence suggests that it may be efficacious in the treatment of adolescents with bulimia nervosa. Multifamily therapy for anorexia nervosa provides a more intensive experience for families needing additional support. This review outlines the three phases of treatment, key tenets of family-based treatment, and empirical support for FBT. In addition, FBT in higher levels of care is described, as well as challenges in the implementation of FBT and recent adaptations to FBT, including offering additional support to eating-disorder caregivers. Future research is needed to identify families for whom FBT does not work, determine adaptations to FBT that may increase its efficacy, develop ways to improve treatment adherence among clinicians, and find ways to support caregivers better during treatment. Keywords: eating disorders, adolescents, family-based therapy, anorexia nervosa, bulimia nervosa